2013
DOI: 10.1111/jvim.12181
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Quality of Life, Clinical, Radiographic, Echocardiographic, and Laboratory Variables in Dogs with Myxomatous Mitral Valve Disease Receiving Pimobendan or Benazepril: The QUEST Study

Abstract: Background: Myxomatous mitral valve disease (MMVD) is an important cause of morbidity and mortality in dogs. Objectives: To compare, throughout the period of follow-up of dogs that had not yet reached the primary endpoint, the longitudinal effects of pimobendan versus benazepril hydrochloride treatment on quality-of-life (QoL) variables, concomitant congestive heart failure (CHF) treatment, and other outcome variables in dogs suffering from CHF secondary to MMVD.Animals: A total of 260 dogs in CHF because of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…There is a reduction in heart size in dogs with MMVD and DCM administered pimobendan. Earlier studies have only evaluated the effect of initiation of pimobendan on dogs’ heart size after the onset of heart failure in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is a reduction in heart size in dogs with MMVD and DCM administered pimobendan. Earlier studies have only evaluated the effect of initiation of pimobendan on dogs’ heart size after the onset of heart failure in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 94%
“…Longitudinal effects of pimobendan treatment have been described in dogs with stage C MMVD but have not been reported in dogs with stage B disease. Some dogs show subtle signs associated with their cardiac disease before overt signs of CHF develop.…”
mentioning
confidence: 98%
“…The median survival times of dogs with moderate and severe congestive heart failure (CHF) was 33 and 9 months, respectively (5). Dogs receiving pimobendan instead of benazepril hydrochloride, additionally to diuretics, have significantly longer survival times (16). The quality of life was similar in dogs receiving pimobendan or benazepril, but the time to increase the treatment regime was longer in pimobendan group, heart size was smaller and water retention was less in the pimobendan group (17).…”
Section: Natural History Of the Diseasementioning
confidence: 94%
“…The biggest trial to date examining pimobendan therapy in dogs with MMVD in CHF has shown survival benefits when compared to ACEi. 5 Previous smaller studies have also shown positive survival benefits. 2,13 However, the veterinary literature evaluating the proarrhythmic effects of pimobendan in dogs with CHF due to MMVD is sparse and conflicting.…”
Section: Figurementioning
confidence: 91%
“…2 Similarly, the QUEST study demonstrated a prolonged time to reach the composite primary endpoint of cardiac death, euthanasia as a consequence of cardiac disease, or treatment failure with pimobendan, and also documented no difference in incidence of arrhythmia compared to benazepril. 5 However, analysis of arrhythmias in the study was limited to a 3 min in-hospital electrocardiogram (ECG), and the number of dogs experiencing sudden death in each group was small. In a study evaluating dogs treated with pimobendan or ACE inhibitor (ACEi), both groups had increased VPCs and atrial premature complexes (APCs) over the duration of the study based on 5-min ECG in a small number of dogs.…”
Section: Introductionmentioning
confidence: 99%